APLIKASI PERMAINAN ‘FIX YOU’ SEBAGAI PENGENALAN MENTAL HEALTH TERHADAP ANAK PANTI ASUHAN - Septian Enggar Sukmana; Cahya Rahmad; Annisa Puspa Kirana; Moch. Zawaruddin Abdullah; Bagas Satya Dian Nugraha; Subhan Indra Prayoga (Jurnal Pengabdian kepada Masyarakat, 2025)
Lack of education and knowledge about mental illness in Indonesia leads to wrong handling of its sufferers. To raise public awareness epescially for orphan, there is a need for an educational medium that is easily accessible and attractive. One solution is to use games, because this medium is more interesting and interactive. A visual novel game with a light storyline and interesting characters can provide education on how to deal with people with potential mental illness. This game uses fuzzy logic to generate different endings based on the player's dialogue choices. The results of the test on 53 respondents showed an average interpretation of 87.36% on the Likert scale, which indicates that this game is highly accepted by users.